The significance of myths associated with natural heritage tourism destinations in Zimbabwe: a case study of Nyanga Mountain, Eastern Zimbabwe - Blessing Muchenje; Gilbert Pwiti; Alick Mhizha (Cogent Social Sciences)
This article examines the role of myths in influencing the cultural and environmental significance of Nyanga Mountain, a natural heritage site in Zimbabwe’s Manicaland province. Recognizing that natural tourism destinations often develop unique cultural identities through myth, this study uses qualitative methods, including in-depth interviews with community members, tour guides, tourists and experts, to explore the role of myths in destination management. Findings indicate that these myths act as cultural tools, enhancing behavioural norms and environmental preservation through taboos and traditional beliefs. The study recommends strategies to preserve these heritage sites, promote cultural values and empower local custodians, supporting sustainable site management and enhancing the site’s cultural and ecological integrity.